Modern Treatment Methods for Acnes. (Progress Annals: Journal of Progressive Research, 2025)
Acne, a common dermatological condition, affects individuals of all ages, causing physical and psychological distress. This article explores modern treatment methods, analyzing their effectiveness and potential side effects. It provides insights from contemporary literature and outlines innovative approaches in dermatology to address acne